Transformation of Cellular Factor XIII into an Active Zymogen Transglutaminase in Thrombin-Stimulated Platelets - Muszbek, László; Haramura, Gizella; Polgár, János (Thrombosis and Haemostasis, 1995)
The cellular form of blood coagulation factor XIII (FXIII) is present in platelets, monocytes and macrophages. During long-term stimulation of platelets by thrombin cellular FXIII becomes activated and crosslinks proteins, however, the mechanism of its activation has not been elucidated. It was shown that, contrary to plasma FXIII, the intracellular activation of platelet FXIII does not involve proteolysis. FXIII remained intact in thrombin-activated platelets, i.e., the activation peptide was not removed from the molecule. Part of the zymogen FXIII molecules, however, assumed an active configuration as was demonstrated both by the measurement of transglutaminase activity and by active-site-SH titration. These findings clearly indicate that during platelet activation, when intracellular Ca2+ concentration is raised, a slow non-proteolytic transformation of FXIII zymogen into an active transglutaminase occurs.